Effect of Leadership Style, Interpersonal Communication and Organizational Commitment on Employee Performance - Noervika Dewi, Nida; Ridwan Kurniawan, Muhamad Syafi’i; Dyahrini, Wien (International Journal of Artificial Intelligence Research, 2022)
This study aims to find out and analyze the influence of leadership style, interpersonal communication and organizational commitment on the performance of staff at SMA IT Ibadurrohman. The employees referred to in this study are all human resources who work at Ibadurrohman IT High School consisting of educators, administrative staff and non-educators. The research method used is quantitative by using multiple linear regression analysis. The population in this study was 31 people so that the total population was sampled as respondents in this study. Data collection was carried out using research instruments in the form of questionnaires measured using a likert scale. Based on the results of data testing, there are several findings as a result of research that show (1) leadership style affects employee performance by 48.4%, (2) interpersonal communication affects the performance of female entrepreneurs by 47.3%, (3) organizational commitment affects employee performance by 17.7%, and (4) together leadership style, interpersonal communication. Organizational commitment affects the performance of employees at Ibadurrohman IT High School.